2020
DOI: 10.3390/plants9070820
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Sequencing Facilitates Discovery of New Plant Viruses in Poland

Abstract: Viruses cause epidemics on all major crops of agronomic importance, and a timely and accurate identification is essential for control. High throughput sequencing (HTS) is a technology that allows the identification of all viruses without prior knowledge on the targeted pathogens. In this paper, we used HTS technique for the detection and identification of different viral species occurring in single and mixed infections in plants in Poland. We analysed various host plants representing different families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 75 publications
1
27
0
Order By: Relevance
“…Mixed infection of plants with several viruses belonging to different taxa is now frequently detected, especially thanks to the application of massive parallel sequencing [24][25][26][27][28]. In this work, the analysis of leaf samples from tomato and pepper indeed revealed mixed infections of PVY (a potyvirus) and other viruses (from the Cucumovirus, Carlavirus, and/or Ophiovirus genera, Table 1) further confirming the complexity of the virome that can be present in single plants [29,30].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Mixed infection of plants with several viruses belonging to different taxa is now frequently detected, especially thanks to the application of massive parallel sequencing [24][25][26][27][28]. In this work, the analysis of leaf samples from tomato and pepper indeed revealed mixed infections of PVY (a potyvirus) and other viruses (from the Cucumovirus, Carlavirus, and/or Ophiovirus genera, Table 1) further confirming the complexity of the virome that can be present in single plants [29,30].…”
Section: Discussionsupporting
confidence: 67%
“…However, to unambiguously assign an isolate to a strain or to identify a divergent variant, a full-length genome characterization is required. The use of high-throughput sequencing (HTS) technologies has brought forth the possibility of unbiased virus detection and identification allowing the gain of a potentially complete view of a plant virome including access to full-length genome data [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In our viral disease updates in three major producing areas, WMV was detected in 53% of the samples, MWMV in 6%, PRSV in 4%, and ZYMV in 3%, while CMV was not detected. These results suggest that WMV is the most prevalent aphid-borne virus causing mosaic diseases in these crops in southeastern Spain, as it also seems to be throughout the Mediterranean regions and Europe as a whole [ 14 , 20 , 47 , 48 ]. However, the high prevalence of WMV, in addition to the low occurrence of ZYMV, and even the non-presence of CMV, could be linked to our dates of sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, potyviruses, such as watermelon mosaic virus (WMV), zucchini yellow mosaic virus (ZYMV), and papaya ringspot virus (PRSV), which all belong to the genus Potyvirus , as well as cucumber mosaic virus (CMV, genus Cucumovirus ), among others, are the most commonly reported aphid-borne viruses affecting cucurbit crops [ 11 , 12 , 13 , 14 , 15 ]. WMV was initially described in Israel in 1963 [ 16 ], and subsequently, it has been reported in cucurbits crops from Italy, Tunisia, France [ 17 , 18 ], Spain [ 19 ], and Poland [ 20 ]. Currently, WMV is distributed throughout most of the European continent, and its transmission has been associated to at least 35 different aphids via a non-persistent manner, with the cowpea ( Aphis craccivora ) , cotton ( Aphis gossypii Glover), and green peach ( Myzus persicae Sulzer) aphids being among the most efficient vectors [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies report the finding of sequences of known and previously unknown plant viruses in environmental samples. These studies include sampling of natural vegetation and managed landscapes (Bernardo et al, 2018;Minicka et al, 2020;Thapa et al, 2015), more restricted natural plant species populations (Kamitani et al, 2019;Muthukumar et al, 2009;Susi et al, 2019), water bodies such as lakes, reservoirs, and rivers (Djikeng et al, 2009;Wolf et al, 2020), sewage (Cantalupo et al, 2011;Fernandez-Cassi et al, 2018;Ng et al, 2012), and wastewater (Alhamlan et al, 2013). Table 1 provides five examples of recent metagenomics studies that reported the actual numbers of different unknown plant viruses they detected in environmental samples.…”
mentioning
confidence: 99%